Functional capacity evaluation: Does it change the determination of the degree of work disability?. Issue 1 (January 2015) - Ratzon, Navah Z.; Amit, Yehuda; Friedman, Sharon; Zamir, Shiri; Rand, Debbie
Abstract: Background: Determining the degree of work disability following traffic accidents is very challenging. Functional capacity evaluations (FCEs) are becoming more commonly used in the process of disability assessment. Objectives: This study aimed to assess the agreement of the physicians' decision regarding the degree of work disability in two conditions: 1) based solely on a medical examination 2) based on a combined medical and FCE. Methods: This is a cross-sectional study, with 123 individuals who experienced car accidents; 76 with whiplash-associated disorders and 47 with a hip fracture. All subjects underwent an FCE, filled-in questionnaires and underwent a medical examination. The medical charts of each subject were rated twice and the degree of work disability was determined by orthopedic surgeons and occupational medicine specialists; once based solely on medical files and once based on medical files that included data from the FCE. The agreement was assessed by Intra-Class Coefficients (ICC) and the dependency between the two ratings by McNemar's test. Results: An excellent ICC and significant dependency were found for the percent disability in the hip injury group whereas a fair ICC and a non significant dependency for the percent disability in the whiplash group. Conclusions: The use of FCEs highlights the worker's capacity to perform duties that are part of the physical demands at work. The integration of FCEs into the disability assessment procedure seems to be important especially for whiplash injuries or in cases of discrepancies between the rate of disability determined by the physician to the patient's complaints and participation.